A Model of the Card Payment System and the Interchange Fee - Paul De Grauwe; Laura Rinaldi (Center for Economic Studies and ifo Institute (CESifo), 2002)
We analyse a card payment system to assess the economic impact of the interchange fee. This fee is paid by the bank of the merchant, the acquirer, to the bank of the consumer, the issuer. We build up a mode in order to explore whether the interchange fee can enhance the participation to the system and thus increase the benefits of the system as a whole. We also investigate what kind of incentives the interchange fee provides to the actors of the system. We show that the interchange fee selected by the card associations differs from the one that would be selected by a welfare maximising social planner. Moreover the interchange fee selected by the market is likely to produce a smaller market for cards than the socially optimal one.
Keywords: 330